Short-term effects on tolerability of inhaled hypertonic saline solution and hypertonic saline plus hyaluronic acid in cystic fibrosis patients - Buonpensiero, P.; Tosco, A.; Di Pasqua, M.; De Gregorio, F.; Sepe, A.; Di Pasqua, A.; Terlizzi, V.; Raia, V. (Acta Biomedica Atenei Parmensis, 2014)
Introduction Inhaled Hypertonic saline (HS) solution has been proposed as a new therapy to increase the hydration of the airway surface in patients with CF. Some adverse events such as coughing, narrowing of the airways and salty taste could be modified by the combination of the solution with Hyaluronic acid. Materials and methods 30 children with cystic fibrosis received inhaled HS and inhaled HSHA for two consecutive days. The measurement of predicted FEV1% was performed before the treatment and 30 minutes post inhalation. Outcome The primary outcome was the evaluation of Forced Expiratory volume at first second (FEV1) % of predicted values measured before and after drug exposure (inhalation to HTS and HSHA respectively). Conclusions The administration of HS and HSHA showed a comparable safety profile.